A topology optimization method for collaborative robot lightweight design based on orthogonal experiment and its applications. (20th January 2022) - Liu, Bin; Sha, Liansen; Huang, Kun; Zhang, Wenbin; Yang, Hongbo
Topology optimization is an effective method for the lightweight of collaborative robots. The extreme working conditions of the robot for the existing topology optimization approach are usually determined by design experience, which may cause mismatch between the chosen load boundary condition of the parts to be optimized and the actual maximum one. In this article, a kind of topology optimization method based on orthogonal experiment was proposed to avoid this mismatch. For this method, the extreme working condition of robots was determined by finding out the combination of robot joint angles when the stress of the part was maximum based on orthogonal experiment. And then, the structure of the part was optimized with the objective of minimizing mass and the constraint of the maximum end displacement of the robots. Finally, the proposed method and the existing method were applied to the lightweight design of a 7 degree of freedom upper limb powered exoskeleton robot, and the results demonstrated that the presented approach can reduce 6.78% maximum end displacement of the robot on average compared with the existing one. It can be concluded that the proposed method in this article is more reasonable and applicable to the structure optimization of collaborative robots.